Discrimination of Panax ginseng from counterfeits using single nucleotide polymorphism: A focused review - Ying, Zheng; Awais, Muhammad; Akter, Reshmi; Xu, Fengjiao; Baik, Sul; Jung, Daehyo; Yang, Deok Chun; Kwak, Gi-Young; Wenying, You (Frontiers in Plant Science, 2022)
Discrimination of plant species, cultivars, and landraces is challenging because plants have high phenotypic and genotypic resemblance. Panax ginseng is commonly referred to as Korean ginseng, which contains saponins with high efficacy on cells, has been reported to have billions of agroeconomic value. The increasing global agroeconomic value of Korean ginseng includes additional species and cultivars that are not Korean ginseng, but have physical characteristics that are very close to Korean ginseng. This almost unidentifiable physical characteristics of Korean ginseng like species are discriminated via the molecular markers. Single nucleotide polymorphism (SNP) is found across the plant species in abundance as a useful tool in molecular mapping of genes and distinguishing a plant species from another. Differentiating the composition of genes in species is quite evident, but the varieties and landraces have fewer differences that are found in addition to single nucleotide mismatch. Especially in the exon region, there exist both favorable and adverse effects in species. Keeping the aforementioned ideas in discriminating ginseng on the basis of molecular markers, SNP has proven itself to be reliable, convenient with advanced markers available out there. This article provides the simplest guidelines that are cost-effective for experiments in traditional laboratory setting to get hands-on SNP marker analysis. Hence, the current review provides detailed up to date information about the discrimination of Panax ginseng exclusively based on SNP adding with a concise method is explained which can be followed to perform the analysis.